2019
DOI: 10.14207/ejsd.2019.v8n3p282
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Buen Vivir in Ecuador: An Analysis of the Stakeholders’ Discourses

Abstract: Buen vivir is a central notion in Ecuador and was introduced in its Constitution in 2008. On the individual level, this notion describes a multidimensional form of well-being, integrating strong cultural and ecological aspects based on indigenous communities’ knowledge. On the national scale, buen vivir is the key notion of public policies and justifies an intervention of the state in all dimensions of sustainable development. The implementation of buen vivir in a developing country as Ecuador raises questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The Correa government became notorious for criminalizing and demeaning such voices, which had previously helped bring it to power [ 38 ]. One qualitative study [ 40 ] identified a group of stakeholders outside of the public sector and not involved in the implementation of PNBV who were more critical of the implementation of PNBV. For example, one stakeholder was critical of Correa’s turn towards extractivism in 2012, which is echoed in other articles that highlight his government's aggressive promotion of mining, oil and gas extraction, and agroindustry [ 16 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Correa government became notorious for criminalizing and demeaning such voices, which had previously helped bring it to power [ 38 ]. One qualitative study [ 40 ] identified a group of stakeholders outside of the public sector and not involved in the implementation of PNBV who were more critical of the implementation of PNBV. For example, one stakeholder was critical of Correa’s turn towards extractivism in 2012, which is echoed in other articles that highlight his government's aggressive promotion of mining, oil and gas extraction, and agroindustry [ 16 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one stakeholder was critical of Correa’s turn towards extractivism in 2012, which is echoed in other articles that highlight his government's aggressive promotion of mining, oil and gas extraction, and agroindustry [ 16 , 37 ]. In another interview, a government stakeholder argued that extractivism in the short term was necessary to finance a reduction in poverty [ 40 ], echoing a common narrative in Correa’s public service (and public speeches) that helped to dismiss resistance to resource extraction as ‘infantile’ or insufficiently informed by science [ 38 ].…”
Section: Discussionmentioning
confidence: 99%